Konsep keluhuran Al-Quran sebagai perlembagaan hidup dan manifestasinya terhadap rahmat sekalian alam / Muhammad Fahmi Md Ramzan and Nurfarhana Mohd Daud - Md Ramzan, Muhammad Fahmi; Mohd Daud, Nurfarhana (Univeristi Teknologi MARA, Sabah, 2019)
This article discusses the concept of the greatness of the Quran as a miracle as well as the main source which is supposed to be a constitution of life. The Quran is not only a guide to the lives of Muslims, it is also a guide and a lifeline to all humanity and even to the jinn. Therefore, the Quran is a blessing to all the world through its teachings as well as the knowledge it contains. The grace of the Quran is in line with the revelation of the Quran to His Prophet who is also a universal mercy. Therefore, this article seeks to dig into the evidence that shows the Quran is a great miracle and a guide for life and mercy for all the world.